The effect of PGPR (Plant Growth Promoting Rhizobacteria) Pseudomonas fluorescens and Bacillus subtilis On Leaf Mustard Plant (Brassica juncea L.) Infected by TuMV (Turnip Mosaic Virus) - Bogi Diyansah; Luqman Qurata Aini; Tutung Hadiastono (University of Brawijaya, 2012)
AbstractOne problem that causing leaf mustard yield loss is the infection of Turnip Mosaic Virus (TuMV). Thevirus causes mild mosaic leaf with vein clearing, blister, malformation and stunting. The use of Plant Growth Promoting Rhizobacteria (PGPR) such as Pseudomonas fluorescens and Bacillus subtilis is oneeffort that could be used to solve the problem. Through the mechanism of induced resistance, thesebacteria can elicit the defense signal in plant for the defence against pathogens. In this study the use of Pseudomonas fluorescens and Bacillus subtilis was performed to test their benefit on leaf mustard planthealth against TuMV infection. This study was conducted with a randomized block design (RBD) byusing 8 treatments and 4 replications. On the experiment of the effect of PGPR on the root length ofleaf mustard plants, the design used was a completely randomized design (CRD) with 4 treatments and4 replications. Leaf mustard plants inoculated with Pseudomonas fluorescens and Bacillus subtilis hadlonger roots than those without the inoculation of Pseudomonas fluorescens and Bacillus subtilis. Inaddition, Pseudomonas fluorescens and Bacillus subtilis was also able to reduce the incubation periodand disease intensity of TuMV on the leaf mustard plant. The activity of catalase enzyme and phenolcontent was elevated in the leaf of leaf mustard plant inoculated with PGPR. The results suggested thatcatalase and phenol production probably play a role in plant defense of leaf mustard against theinfection of TuMV.Key word : Mustard, Turnip Mosaic Virus (TuMV), PGPR